On the Harvesting of Age Structured of Fish Populations - Behncke, H.; Al-Nassir, Sadiq (Communications in Mathematics and Applications, 2017)
The yearly cycle of marine fish suggests to describe such populations by a discrete time dynamical Leslie model. The only nonlinear input into this model is the recruitment functions. Its influence on the stability of equilibria is investigated. We show that a monotone recruitment function leads to globally stable equilibria. Harvesting is introduced as fishing mortality so that the structure of the underlying model remains the same. The impact of the recruitment function is also discussed.